English Language Teaching Today Linking Theory and Practice - Renandya, Willy A.; Widodo, Handoyo Puji (English Language Education, 2016)
English Language Teaching Today: Linking Theory and Practice provides an up-to-date account of current principles and practices for teaching English in the world today. The chapters, written by internationally recognized language teacher educators and TESOL specialists, introduce the reader to key language skill areas (i.e., listening, speaking, reading, writing, pronunciation, grammar and vocabulary) and explain how each skill area can be taught in a principled manner in diverse language learning contexts. Throughout the book, the link between theory and practice is explicitly highlighted and exemplified.  This reader-friendly book is suitable for undergraduate and graduate students enrolled in TESOL and other second language education programmes as well as for TESOL professionals who wish to stay current with recent developments in ELT.